The Social Dimensions of Adjustment : A General Assessment - World Bank (Washington, DC, 2012)
Inevitable as structural adjustment has been, and successful as it might be, the engagement with poverty in Africa is going to be a long-term affair. If growth does not restart, the reverse trickle-down may further jeopardize the most vulnerable groups in the population, involving high transitional costs of adjustment. Those costs arise from the reduction in real incomes engendered by tighter monetary and fiscal policies, from increased unemployment resulting from lags in supply responses, from price adjustment in product and factor markets, and from reduced availability of social services following the contraction of public expenditures. The Social Dimensions of Adjustment (SDA) program is to be reviewed as a strategic reaction to that nascent concern about the position of the poor in the process of structural adjustment. It is seen as a catalyst of effective action aimed at poverty reduction in the framework of structural adjustment programs. SDA delineated four components: analytical research, information gathering, social action programs, and institution building and training. This paper examines each of the major SDA components and attempts to elaborate on the distinction between conjunctural (adjustment-vulnerable) and structural (long-term) poor and incorporates a high level of analysis as well as specific innovations which are likely to withstand the test of time professionally.